A Study on Mural Paintings of Yozgat Tokmak Hasan Pasha Mosque - Begüm Buğdaycı (Art-Sanat)
Tokmak Hasan Pasha Mosque is one of the buildings that attract attention in Anatolia with its mural paintings. A total of six mural paintings are available to decorate the structure. Three depictions of the murals, Mizan, Âlem-i lâhût and Livâü’l-Hamd, have their subjects taken from manuscripts with religious content such as Muhammadiye and Mârifetnâme. Apart from those, the Blue Mosque (Sultan Ahmet), Mecca and a carpet depiction painted on the intersection of two walls are included in the painting repertoire. During the restoration of the mosque, which was completed in 2022, Arabic and Latin alphabet scripts, various notes and hand-drawn decorations have been revealed under the plaster. The most important data obtained in these endeavors was the artist’s inscription on the western wall of the harem. According to the inscription, it is acknowledged that the murals were performed in 1950 by an artist named Muhsin Bali. The depiction of the Mizan, one of the mural paintings, differs in terms of being painted together with elements such a mosque, oil lamp and mimbar as well as the use of scripts. The depiction of the universe is of utmost importance in terms of its one-to-one depiction with the miniature in Mârifetnâme. The depiction of Livâü’l-Hamd, which appears only in Islamic works and hadiths, was also taken as an example from the painting on the subject of “Mirat-i Mahşer” in Muhammediye and the inscriptions on the flag arms have also been included. The depiction of the Blue Mosque (Sultan Ahmet) is depicted in the same view as the view from the northwest corner of the building and has been processed with almost true form to the architectural elements of the original building. Although the depiction of Mecca reflects the 20th century with its use of color and advanced perspective understanding, it still maintains traces of the miniature tradition. The depiction of the carpet engraved on the intersection of two walls is processed in a similar style with another example that we are aware of.